How Safe is Vehicle Safety? The Contribution of Vehicle Technologies to the Reduction in Road Casualties in France from 2000 to 2010 - Page, Yves (Association for the Advancement of Automotive Medicine, 2011)
In France, over the last 10 years, road fatalities have decreased dramatically by 48%. This reduction is somewhat close to the target fixed by the European Commision in 2001 for the whole of Europe (−50 %). According to the French govnerment, 75% of this reduction was due to the implementation of automatic speed cameras on the roadsides from 2003 onwards. Yet, during this period, there was also a significantly increase in safety technology, new regulations in front and side impacts, and developments in Euro NCAP to improve passive safety in the vehicles. This paper set out to estimate the extent that vehicle safety technologies contributed to the road safety benefits over this decade. Using a combination of databases and fitment rates, the number of fatalities and hospitalized injuries saved in passenger car crashes was estimated for a number of safety technologies, individually and as a package including a 5 star EuroNCAP rating. The additional benefits from other public safety measures were also similarly estimated. The results showed that overall safety measures during this decade saved 240,676 fatalities + serious injuries, of which 173,663 were car occupants. Of these, 27,365 car occupants and 1,083 pedestrian savings could be attributed directly to vehicle safety improvements (11% overall). It was concluded that while public safety measures were responsible for the majority of the savings, enhanced vehicle safety technologies also made a significant improvement in the road toll in France during the last decade. As the take-up rate for these technologies improves, is expected to continue to provide even more benefits in the next 10-year period.